Elimination of cross-reactivity by addition of an excess of cross-reactant for radioimmunoassay of 17alpha-hydroxypregnenolone - Hill, M; Hampl, R; Lukác, D; Lapcík, O; Pouzar, V; Sulcová, J (Steroids, 1999)
Polyclonal antiserum against 3beta,17alpha-dihydroxypregn-5-en-20-one-19-O-(carboxymethyl )-oxime bovine serum albumin (17alpha-hydroxypregnenolone-19-CMO:BSA), was raised in rabbits. Its main structural determinants were the substituents on D-ring as demonstrated by its 107% cross-reaction with 17alpha-hydroxyprogesterone. This unspecificity was almost completely eliminated by addition of the excess of the cross-reactant directly to the analytical system. The contribution of the cross-reactant from the sample in such a system became negligible due to saturation of the populations of polyclonal antibodies recognizing the analyte as well as the cross-reactant. The possible interference of 17alpha-hydroxypregnenolone-3-sulfate was avoided by inserting ether extraction. The analytical system appeared to be stable to differences in cross-reactant concentrations even in samples from patients with pathologically elevated serum levels of 17alpha-hydroxyprogesterone. The radioimmunoassay was compared with the system using the unspecific antiserum alone, but after separation of the cross-reactants by HPLC. As demonstrated by parallel measurement of 125 samples of human plasma from both sexes and various ages either before and/or after adrenocorticotropin stimulation and 17 samples with elevated basal of human plasma 17alpha-hydroxyprogesterone levels, an excellent correlation was achieved between both methods. The method, based on a simple addition of the cross-reactant, avoids the time-consuming chromatographic separation and, in comparison with the other approaches for improving the specificity of polyclonal antisera, is efficient and rapid. Mathematical analysis of the relations in equilibrium demonstrates that such a simple approach is an efficient way for improvement of immunoassay specificity using some polyclonal antisera.
Keywords: radioimunoanalýza; řízení kvality; Radioimmunoassay; Quality Control; Sensitivity and Specificity; mužské pohlaví; Chromatography, High Pressure Liquid; radioizotopy jodu; Tritium; vysokoúčinná kapalinová chromatografie; tritium; 17-alfa-hydroxypregnenolon; ženské pohlaví; 17-alpha-Hydroxypregnenolone; Humans; senzitivita a specificita; Female; Iodine Radioisotopes; lidé; Male